Hematology, Cytochemistry and Ultrastructure of Blood Cells in Common Palm Civet (Paradoxurus hermaphroditus) - Chaleow Salakij; Jarernsak Salakij; Nual-Anong Narkkong; Daraka Tongthainun; Kreangsak Prihirunkit; Sommas Itarat (Agriculture and Natural Resources, 2007)
Hematology and blood cells from 4 adult common palm civets (Paradoxurus hermaphroditus) in Khaokeaw Open Zoo were prepared for morphology, cytochemistry and ultrastructure observations. There was no blood parasite in all civets. The red blood cells showed relatively uniform in size, with 4.3 μm mean diameter. Neutrophils had tight constricted, multilobed nuclei and contained many specific granules which clearly detected by transmission electron microscope (TEM). Neutrophils stained strongly positive with Sudan black B (SBB) and peroxidase (PO) but negative with alpha-naphthyl acetate esterase (ANAE) and β-glucuronidase (βG). By scanning electron microscope (SEM), they showed many microvilli and some micropores. Eosinophils contained numerous large round red refractive granules and stained strongly positive with SBB and PO, but negative with ANAE and βG. By SEM, the granule contour of eosinophil was most easily delineated from the other granulocytes. Ultrastructurally, they contained large round granules with homogenous content without crystalloid-core. Basophils had variable numbers of dull grey, pleomorphic granules and were negative for SBB and PO, but strongly positive for ANAE and moderately positive for βG. By SEM, the surface of basophil was smooth with small granule contour. Ultrastructurally, they contained smaller, homogenous and less electron-dense granules than those in the eosinophils. Lymphocytes were negative for SBB and PO but had 2 patterns of reactivity for ANAE and βG, including focal dot and fine granular staining. Monocytes were negative for SBB, PO and βG but moderately positive for ANAE. The large round eosinophil granules were the characteristic of leukocytes in common palm civet.